High throughput method for analysis of repeat number for 28 phase variable loci of C. jejuni strain NCTC11168 - Lango-Scholey, Lea; Aidley, Jack; Woodacre, Alex; Tretyakov, Michael; Jones, Michael A.; Bayliss, Christopher D. (Public Library of Science, 2016)
Mutations in simple sequence repeat tracts are a major mechanism of phase variation in several bacterial species including Campylobacter jejuni. Changes in repeat number of tracts located within the reading frame can produce a high frequency of reversible switches in gene expression between ON and OFF states. The genome of C. jejuni strain NCTC11168 contains 29 loci with polyG/polyC tracts of seven or more repeats. This protocol outlines a method for rapidly determining ON/OFF states of these 28 phase-variable loci in a large number of individual colonies. The method combines a series of multiplex PCR assays with a GeneScan assay and automated extraction of tract length, repeat number and expression state. This high throughput, multiplex assay has utility for detecting shifts in phase variation states within and between populations over time and for exploring the effects of phase variation on adaptation to differing selective pressures. An important output of this assay is combinatorial expression states that cannot be determined by other methods. This method can be adapted to analysis of phase variation in other C. jejuni strains and in a diverse range of bacterial species.